Kajian Penerapan Cara Pembuatan Obat Tradisional yang Baik pada Industri Ekstrak Bahan Alam di Indonesia - Purnama Dwi Tistiyanto; Sukrasno Sukrasno; Budiastuti Budiastuti; Lydia Prima (UIN Syarif Hidayatullah Jakarta, 2023)
Good Manufacturing Practices for Traditional Medicine (GMP for TM) must be applied by Traditional Medicine Businesses in Indonesia, namely Traditional Medicine Small Businesses (TMSB), Traditional Medicine Micro Businesses (TMMB), Traditional Medicine Industry (TMI) and Active Traditional Medicine Ingredients Industries (ATMII), to ensure the quality of the products produced. At the end of 2021, the Indonesian FDA established the most recent GMP for TM standards, which follow the PIC / PE 009-015 standard that must be applied by TMI and ATMII, with an appendix related to GMP for Active Ingredients Traditional Medicine (ATMI) for ATMII. This study aims to determine the GMP profile for TM implementation, specifically in 17 ATMII in Indonesia, and to provide recommendations to the Indonesian FDA in supervising and assisting ATMII. The method was carried out by creating a list of questions from 17 aspects of GMP for Active Ingredients TM, including aspects of product development and technology transfer, to be filled out independently by 17 IEBA, followed by verification and assessment of compliance with the implementation of GMP for TM with the conclusion of the assessment results of the categories are very good, good, sufficient, and poor. According to the findings of the current GMP for TM application, 6 ATMII (35.3%) received a very good assessment result, 6 ATMII (35.3%) received a good assessment result, 3 ATMII (17.6%) received sufficient assessment results, and 2 ATMII (11.8%) received poor assessment results. The current GMP for TM implementation by ATMII that requires attention are Contract Manufacturers (Including Laboratories), product development and technology transfer, personnel, quality control, and validation, whose average level of fulfilment is still less than 80%. These aspects are critical because they significantly influence the consistency of the quality.